A new species of Sistotremastrum (Sistotremastrales, Basidiomycota) from subtropical China - Hou, Li-Xin; Li, Xiang-Lin; Luo, Kai-Yue; Dai, Yu-Cheng; Yuan, Yuan; Zhou, Meng (Phytotaxa, 2025)
The species of Sistotremastrum are wood decay fungi, distributed worldwide. During a survey of fungi in mixed forests in Guizhou and Zhejiang Provinces, China, a new species, Sistotremastrum massonianum was described based on morphological characteristics and molecular evidence. Morphologically, this new species is characterized by farinaceous basidioma, grandinoid to odontoid hymenial surface, basidia with four sterigmata and narrowly ellipsoid to broadly cylindrical basidiospores 3.3–4.8 × 2.1–2.8 µm. The two-gene (ITS+nLSU) analysis of the genus Sistotremastrum indicated that S. massonianum represents a significantly supported monophyletic group, which is clustered with S. aculeatum, S. aculeocrepitans, S. denticulatum, and S. geminum.